AGILE DEVELOPMENT OF A PROJECT BASED LEARNING MANAGEMENT APPLICATION: A SCRUM DRIVEN STRATEGY TO ENHANCE EDUCATIONAL OUTCOMES - Reisa Permatasari; Bonda Sisephaputra (Universitas Trilogi, 2025)
Programming education at the Faculty of Engineering, Surabaya State University, faces challenges including low student engagement, ineffective teaching methods, and difficulties in monitoring progress. This study proposes the adoption of the Scrum methodology to develop a Project-Based Learning Management Application (PBLMA) tailored for programming courses. The Scrum framework, with its iterative sprints and emphasis on collaboration, facilitates the development of a flexible, user-centered application. By integrating sprint retrospectives, the development process ensures continuous improvement, aligning the PBLMA with the dynamic needs of educators and students. Results demonstrate that Scrum enables efficient development, with iterative cycles allowing for rapid adaptation to feedback. The application enhances student engagement and simplifies progress tracking, addressing key educational challenges. This study highlights Scrum’s potential as a robust framework for educational software development, offering insights for future implementations in academic settings